2017
DOI: 10.5137/1019-5149.jtn.18839-17.3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of morphologic and morphometric characteristic of foramen transversarium on 3-dimensional multidetector computed tomography angiography (mdcta)

Abstract: We believe that the determination of foraminal variations could be an important guide for neurosurgeons and radiologists in the diagnosis and treatment of diseases in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
5
0
5
Order By: Relevance
“…Vertebral artery variations are also not an unusual finding. The most usual entry point of the artery in the spine is the C 6 vertebra [22,23], but entrance of the artery in the C 4 , C 5 , and C 7 vertebra has been also reported [5,6,18,23]. Wakao et al [5] observed a C 4 level of entrance in 1.1%, a C 5 Table 4 Coexisting variations of the foramen transversarium in patients exhibiting asymmetry in the vertebral artery level of entrance in 6.2%, and a C 7 level of entrance in 1.5% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral artery variations are also not an unusual finding. The most usual entry point of the artery in the spine is the C 6 vertebra [22,23], but entrance of the artery in the C 4 , C 5 , and C 7 vertebra has been also reported [5,6,18,23]. Wakao et al [5] observed a C 4 level of entrance in 1.1%, a C 5 Table 4 Coexisting variations of the foramen transversarium in patients exhibiting asymmetry in the vertebral artery level of entrance in 6.2%, and a C 7 level of entrance in 1.5% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…No estudo da anatomia do FT, Taitz (CAGNIE et al, 2005;DEǦIRMENCI;YILMAZ, 2013;METIN TELLIOGLU et al, 2018;TAITZ;NATHAN;ARENSBURG, 1978).…”
Section: Variações Anatômicasunclassified
“…Observamos que houve maior similitude entre os estudos recentes, ao identificar os níveis com maior ou menor DAP, sendo em C6 o maior DAP encontrado e, em C7, o menor (GUPTA et al, 2014;METIN TELLIOGLU et al, 2018;ZIBIS et al, 2018 Bruneau et al (2006) que obtiveram a AF aplicando a fórmula geométrica (A=π * M/2 * m/2) para elipses (forma oval regular), baseada em dois eixos principais do forame, maior e menor. No entanto, observamos, em nosso estudo, que os forames não possuem forma regular constante, já que as irregularidades na sua borda podem não expressar um resultado real da sua área.…”
Section: Variações Anatômicasunclassified
See 2 more Smart Citations